Theoretical and methodological aspects in evaluating morphological productivity in corpus languages: A case study on Hittite word-formation - Rossi, Alessandro (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2025)
-